Role of Media for Stop Environmental Change - Jha, Rudra (Journal of Advanced Research in Journalism & Mass Communication, 2022)
At this point in time, the media plays a significant part in the effort to halt the progression of environmental change. Public awareness is the most important factor in the fight to rescue the environment and the media plays a crucial role in both public awareness and communication. In the present time digital media is extremely important. The term “environmental change” refers to the environment through which natural systems lose their equilibrium. The natural cause and the cause that humans have manufactured account for the majority of environmental changes. Natural causes include things like volcanic eruptions, shifts in the earth’s orbit, ocean currents and variations in the sun, whereas man-made causes include things like deforestation, coal mining, greenhouse gases, agriculture and the combustion of fossil fuels. The quantity of environmental change continued to grow on a daily basis as a condition of the following: a rise in sea level; heavy rainfall; conditions of flooding; drought; a reduction in agricultural production; a change in the ecosystem; a rise in temperature; acid rain; the melting of ice; and so on. Therefore, we have an environment to protect our natural resources. It is of the utmost importance to educate people about how they may help conserve our environment. The media had an important role in the coverage of environmental issues.